2011
DOI: 10.1093/ndt/gfr697
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of the impact of erythropoiesis-stimulating agents on fatigue in dialysis patients

Abstract: Partial correction of anemia with ESA results in improvement of fatigue among patients on dialysis, most strikingly in those patients with baseline Hb levels <10 g/dL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
2
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(64 citation statements)
references
References 28 publications
1
59
2
2
Order By: Relevance
“…erythropoietin) can be a good thing when used for appropriate medical reasons (e.g. to combat anaemia and fatigue in dialysis patients) [57]. The current pandemic of physical inactivity [58] and the associated burden of disease [2] seem to me valid medical reasons for more psychobiological, clinical and ethical research on the use of psychoactive drugs to facilitate physical activity behaviour.…”
Section: Resultsmentioning
confidence: 99%
“…erythropoietin) can be a good thing when used for appropriate medical reasons (e.g. to combat anaemia and fatigue in dialysis patients) [57]. The current pandemic of physical inactivity [58] and the associated burden of disease [2] seem to me valid medical reasons for more psychobiological, clinical and ethical research on the use of psychoactive drugs to facilitate physical activity behaviour.…”
Section: Resultsmentioning
confidence: 99%
“…In randomized controlled trials (RCTs), it was found that the vitality score [20], frequency of blood transfusion [21], and fatigue score [22] in the Medical Outcomes Study 36-Item Short-Form Health Survey (SF-36) of QOL assessment were improved with the increase in Hb level. Although the results of some meta-analyses and the re-analysis of RCTs that have been recently published negate the idea that high Hb levels improve QOL [23][24][25], they suggested that QOL can be improved when Hb levels are increased up to 10 g/dL in patients with Hb levels <10 g/dL [23].…”
Section: Statementmentioning
confidence: 99%
“…The use of ESA has beneficial effects by correcting anemia and their associated symptoms and improving patients' quality of life [50,51]. However, the effects of ESA on the progression of renal function are controversial.…”
Section: Erythropoiesis-stimulating Agents In Ckd-anemiamentioning
confidence: 99%